EDUCATIONAL CHARACTER VALUES IN ACEH FOLK STORIES: BANTA BARENSYAH AS AN INVENTION FOR TEACHING MATERIALS IN SCHOOL - Fitriyah, Mahmudah; Bahtiar, Ahmad; Suparno, Darsita (Universitas PGRI Sumatera Barat, 2025)
Folklore is a local wisdom that contains many Indonesian cultural values. Many folk tales tell stories about people's lives and tell history or societal figures, accompanied by values that are very good if taught in schools. Acehnese folklore is a form of oral literature transmitted by word of mouth, containing messages or advice from experiences or natural events linked to events experienced by humans, ancestors, or pious people at that time. This research aims to describe the values of character education in the Acehnese folklore Banta Barensyah. This story is full of character education values from which many lessons can be learned to become role models for today's young generation. The story of the hard work and love between parents and children is so beautifully described, right up to the story's happy ending. This research uses a qualitative descriptive method, with data collection techniques in the form of listening and note-taking techniques, as well as data analysis techniques in the form of content analysis. Based on the study carried out, there are 13 educational character values in this folklore, including: 1) religiosity; 2) honesty; 3) hard work; 4) creativity; 5) independent; 6) democratic; 7) curiosity; 8) national spirit; 9) appreciates achevements; 10) friendly/communicative; 11) love of peace; 12) social care; and 13) responsibility. So, it can be concluded that the Acehnese folklore Banta Barensyah is very good to use as teaching material for Indonesians and schools.